IMPLEMENTASI KEBIJAKAN PROGRAM PEMBINAAN DINAS SOSIAL TERHADAP ANAK JALANAN DI KOTA BATAM - Kartini, Eka; Dedi Epriadi (LPPM Universitas Putera Batam, 2022)
The coaching program implemented by the Batam City Social Service is very important so that street children who live on the streets get their proper place. Through this research, the author aims to find out how the implementation of the guidance carried out by the Social Service and Batam City and to find out the inhibiting factors that affect the implementation of the street children development program in Batam City. Judging from the data obtained, there are several problems from the implementation process, including, the number of street children which is increasing every year, facilities and infrastructure, limited number of employees, and the problem of mentally disturbed children. The method used in this study uses qualitative research with a descriptive approach to obtain relevant and valid data in conducting a study. From this study, the authors involved 9 informants from parties related to the street children development program in Batam City.The Batam City Social Service in implementing the street children development program has implemented it in accordance with the applicable rules, it's just that in the implementation process there are still some obstacles so that the process of implementing street children guidance has not gotten the expected results.